2017
DOI: 10.1111/cas.13216
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endothelial Fas expression as a mechanism of promotion of vascular integrity by mural cells in tumors

Abstract: Angiogenesis is a multi‐step process that culminates in vascular maturation whereby nascent vessels stabilize to become functional, and mural cells play an essential role in this process. Recent studies have shown that mural cells in tumors also promote and maintain vascular integrity, with wide‐reaching clinical implications including the regulation of tumor growth, metastases, and drug delivery. Various regulatory signaling pathways have been hitherto implicated, but whether regulation of Fas‐dependent apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…reported that low-doses of TGF-β inhibitor successfully altered the TME including tumor vasculature, which increased the EPR effect with minimal side effects 105. Additionally, TGF-β inhibition in pericyte-abundant BxPC-3 pancreatic cancer vessels increased the uptake of NPs, logically implying the augmented EPR effect 106, 107. The role of other TME-related factors, such as fibroblast growth factor (FGF) and platelet-derived growth factor (PDGF) is under evaluation in terms of TME-remodeling for anti-cancer therapy.…”
Section: Physiological Remodeling Of Tmementioning
confidence: 98%
“…reported that low-doses of TGF-β inhibitor successfully altered the TME including tumor vasculature, which increased the EPR effect with minimal side effects 105. Additionally, TGF-β inhibition in pericyte-abundant BxPC-3 pancreatic cancer vessels increased the uptake of NPs, logically implying the augmented EPR effect 106, 107. The role of other TME-related factors, such as fibroblast growth factor (FGF) and platelet-derived growth factor (PDGF) is under evaluation in terms of TME-remodeling for anti-cancer therapy.…”
Section: Physiological Remodeling Of Tmementioning
confidence: 98%
“…The latter cancer lacks pericyte coverage and is generally more responsive to chemotherapy. 14,15 We also found that while the CT26 colon carcinoma model with little pericyte coverage shows optimal intratumoral nanoparticle accumulation when treated with the angiogenesis inhibitor Sorafenib, the BxPC-3 model responds only to TGF-b inhibition. 16 This suggests that vessel architecture, notably in relation to pericyte coverage, is an important determinant of nanotherapeutic efficacy.…”
Section: Stromal Barriers To Drug Delivery Within the Tme In Pancreat...mentioning
confidence: 65%
“…It is well known that both HNPCs and VECs express Fas/FasL, and IDD angiogenesis is associated with Fas/FasL (Table 1 ). Studies have shown that the regulation of endothelial Fas signaling promotes vascular integrity by mural cells in tumors 69 . Fas-mediated apoptosis plays an essential role in preventing angiogenesis in other tissues 70 , 71 .…”
Section: The Death Receptor Pathway and Iddmentioning
confidence: 99%